2002
DOI: 10.1021/ac0257243
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Dimerization and Chiral Recognition Studied by High-Performance Liquid Chromatography

Abstract: The retention and separation of D,L-dansylvaline enantiomers (used as test solutes) were investigated using silica gel as stationary phase and vancomycin as chiral mobile-phase additive. A retention model was developed to describe the mechanistic aspects of the interaction between solute and vancomycin in the chromatographic system. It considered the formation of vancomycin dimers both "free" in the mobile phase and adsorbed on silica. By fitting the model equation to experimental data, it appeared clearly tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…The portion of vancomycin chiral selector adsorbed on the surface is affected by both the stationary-phase structure and mobile-phase composition, so it need not be necessarily the same on the both columns. 17 An interesting feature influencing the interaction mechanism of analytes with vancomycin as CMPA is the formation of vancomycin dimers in solution, 43,44 as described by many authors. [43][44][45][46][47][48] Experimental approaches as well as computer simulation have been used to characterize the dimer formation.…”
Section: Results and Discussion Enantioselective Separations Of Profementioning
confidence: 99%
See 1 more Smart Citation
“…The portion of vancomycin chiral selector adsorbed on the surface is affected by both the stationary-phase structure and mobile-phase composition, so it need not be necessarily the same on the both columns. 17 An interesting feature influencing the interaction mechanism of analytes with vancomycin as CMPA is the formation of vancomycin dimers in solution, 43,44 as described by many authors. [43][44][45][46][47][48] Experimental approaches as well as computer simulation have been used to characterize the dimer formation.…”
Section: Results and Discussion Enantioselective Separations Of Profementioning
confidence: 99%
“…Moreover, dimer formation, which was reported to improve stereoselective interaction, cannot be expected here. [43][44][45][46][47][48] Surprisingly, relatively good results were obtained for flobufen, as shown in Figure 5. The best enantioseparation of flobufen was achieved with 25% MeOH in the mobile phase for the vancomycin CSP.…”
Section: Enantioseparations Of Profen Nsaids Usingmentioning
confidence: 99%
“…Improved chiral selectivity for flurbiprofen and FMOC-amino acid enantiomers was observed by Sun and Olesik when vancomycin was added to the mobile phase on a vancomycin-bonded chiral column (Chirobiotic-V) [27]. A deeper investigation was carried out by Slama et al [28] through establishing a retention model to describe the interaction between solute and vancomycin in the chromatographic system. They concluded that the formation of back-to-back dimmers on the column was mainly responsible for the greatly improved enantioseparation.…”
Section: Chiral Separation By Simultaneous Use Of Norvancomycin As Chmentioning
confidence: 99%
“…Some fundamental studies on the mechanism of chiral recognition of vancomycin-type glycopeptide antibiotics have been reported [11][12][13][14][15][16][17][18]. The linking position and type of sugar moieties of vancomycin-type glycopeptide antibiotics showed a remarkable influence on their enantiorecognition ability.…”
Section: Introductionmentioning
confidence: 99%
“…The linking position and type of sugar moieties of vancomycin-type glycopeptide antibiotics showed a remarkable influence on their enantiorecognition ability. Many groups also attributed these remarkable effects to the mechanism of dimerization [18,19]. But the role of the chlorine substituents in the vancomycin-type glycopeptide antibiotics for chiral recognition has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%